Contrast enhancement for improved detection of Ananas Comosus from aerial imagery / Wan Nurazwin Syazwani Rahimi, Muhammad Asraf Hairuddin and Megat Syahirul Amin Megat Ali - Rahimi, Wan Nurazwin Syazwani; Hairuddin, Muhammad Asraf; Megat Ali, Megat Syahirul Amin (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
This paper describes contrast enhancement method used in detecting Ananas Comosus from aerial images. The main challenge faced by many researchers is to deal with image under low contrast conditions. Under low contrast, target images of Ananas Comosus often blends with the background features such as leaves and ground, making detection difficult. This study is set out to investigate the usefulness of implementing contrast enhancement technique on existing image to improve detection performance. Aerial images under study were obtained at Simpang Renggam pineapple plantation using DJI Phantom 3 and subjected to two image pre-processing methods-intensity adjustment method and contrast-limited adaptive histogram equalization methods. As a control, these images were also evaluated against pre-processing method without any contrast enhancement. The performance of the techniques for detecting Ananas Comosus is then assessed using relative error, RE and mean absolute percentage, MAPE. The best results were obtained by using contrast-limited adaptive histogram equalization method; yielding RE of 0.125 and MAPE of 0.008% compared to intensity adjustment technique yielding maximum RE of 0.286 and MAPE of 0.027%. Meanwhile detection without image enhancement had resulted maximum RE of 0.250 and MAPE is 0.024%.